Auxiliaries used in the forced eruption of impacted maxillary canines - Hernandez, Sandra Regina C. (The Journal of the Philippine Dental Association)
This report describes the management of impacted maxillary canines in two patients. Treatment began with levelling and aligning of the dentition. Surgery to expose the impacted canine was performed at which time a bond was attached to the tooth. Measures to erupt the canine are discussed here including stainless steel ligature wires, Nitinol auxiliary wires and intra-ora elastics.